Studies on the Preponderance of Jellyfish in Coastal Waters of Veraval - S.K., Panda; V.R., Madhu (Fishery Technology, 2025)
Ascendance pattern of jellyfish biomass in coastal waters off Veraval was investigated. Jellyfish landing figures obtained from four different trawling systems viz. 18m semipelagic trawl with 70mm codend mesh size (SP70), 18m semipelagic trawl with 50mm codend mesh size (SP50), 34m bottom trawl with 60mm codend mesh size (BT60) and 34m bottom trawl with 40mm codend mesh size (BT40) during 2005-06 was used for the analysis. The average percentage contribution of jellyfish varied from 9.7-23.8% in different trawling systems. Exclusion of non-jellyfish hauls revealed highest jellyfish capture (91%) by SP70 and more than 22% in all the trawling systems. The frequency of occurrence of jellyfish was highest in BT40. Estimation of seasonal variation in jellyfish landings showed higher catch during post-monsoon period i.e. 25% considering all hauls and 63% after excluding non-jellyfish hauls. Jellyfish formed higher component of bycatch during pre-monsoon. Juveniles of commercially important species like cephalopods, sciaenids and ribbon fishes were found to have higher degree of association with jellyfish.